Enhancing Teachers’ Competence in AI-Integrated Learning through Participatory Training: A Community Service Program in the Society 5.0 Era - Bea Hana Siswati; Iwan Wicaksono; Mohamad Safwat Ashahri Bin Mohd Salim (Universitas Lambung Mangkurat, 2026)
Digital transformation in education requires teachers to possess adequate competencies in utilizing Artificial Intelligence (AI) to support adaptive and data-driven learning. However, preliminary observations at SMA Negeri 1 Ngoro Mojokerto indicated that AI utilization in classroom practices remained limited. This community service program was therefore implemented as a participatory training initiative to strengthen teachers’ competence in integrating AI into teaching and learning activities. The program employed a Participatory Action Research (PAR) framework as a method for implementing community service, consisting of planning, implementation, reflection, and evaluation stages. Program outcomes were evaluated through comparisons of teachers’ competency scores before and after the training, complemented by observations and reflective discussions. The results demonstrated an increase of more than 45% in teachers’ average competency scores across knowledge, skills, and attitudes toward AI integration. In addition, 85% of teachers successfully developed AI-integrated lesson plans (RPP), and 70% implemented them in classroom learning. Qualitative findings further revealed the emergence of an internal teacher learning community and a shift toward more adaptive and innovative teaching practices. These findings suggest that contextual, practical, and participatory training is an effective strategy for building teachers' capacity to respond to educational challenges in the Society 5.0 era.